EDEM2 initiates mammalian glycoprotein ERAD by catalyzing the first mannose trimming step - Ninagawa, Satoshi (The Rockefeller University Press, 2014)
Glycoproteins misfolded in the endoplasmic reticulum (ER) are subjected to ER-associated glycoprotein degradation (gpERAD) in which Htm1-mediated mannose trimming from the oligosaccharide Man(8)GlcNAc(2) to Man(7)GlcNAc(2) is the rate-limiting step in yeast. In contrast, the roles of the three Htm1 homologues (EDEM1/2/3) in mammalian gpERAD have remained elusive, with a key controversy being whether EDEMs function as mannosidases or as lectins. We therefore conducted transcription activator-like effector nuclease–mediated gene knockout analysis in human cell line and found that all endogenous EDEMs possess mannosidase activity. Mannose trimming from Man(8)GlcNAc(2) to Man(7)GlcNAc(2) is performed mainly by EDEM3 and to a lesser extent by EDEM1. Most surprisingly, the upstream mannose trimming from Man(9)GlcNAc(2) to Man(8)GlcNAc(2) is conducted mainly by EDEM2, which was previously considered to lack enzymatic activity. Based on the presence of two rate-limiting steps in mammalian gpERAD, we propose that mammalian cells double check gpERAD substrates before destruction by evolving EDEM2, a novel-type Htm1 homologue that catalyzes the first mannose trimming step from Man(9)GlcNAc(2).